2008
DOI: 10.3997/1873-0604.2008033
|View full text |Cite
|
Sign up to set email alerts
|

The use of 2D electrical tomography to assess pollution in slurry ponds of the Murcia region, SE Spain

Abstract: A large quantity of pig slurry is produced in the Murcia Province, raising serious environmental concern. Monitoring the evolution of the slurry ponds with time in the subsoil is a prime requirement for environmental safety. Our aim was to determine the temporary effects of pig slurry ponds on the subsoil in the Murcia Province to establish the degree of slurry pond infiltration in semi‐arid climates. A non‐destructive, geophysical, 2D electrical tomography technique was used to: 1) monitor the vertical moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(31 reference statements)
3
9
0
Order By: Relevance
“…Martínez-Pagán et al (2009) [19] pointed out that it is necessary to have information about the physical integrity of slurry ponds to avoid potential risks of environmental pollution. A defective slurry pond can increase eutrophication problems of surface and groundwater with high amounts of PO 4 3− , NO 3 − , and NH 4 + and salinization, phytotoxicity, and nutritional imbalances filtration into aquifers as well as damage to soils.…”
Section: Introductionmentioning
confidence: 99%
“…Martínez-Pagán et al (2009) [19] pointed out that it is necessary to have information about the physical integrity of slurry ponds to avoid potential risks of environmental pollution. A defective slurry pond can increase eutrophication problems of surface and groundwater with high amounts of PO 4 3− , NO 3 − , and NH 4 + and salinization, phytotoxicity, and nutritional imbalances filtration into aquifers as well as damage to soils.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have also demonstrated reasonable correlations between apparent electrical resistivity / conductivity (EC a ) and concentrations of various chemicals in groundwater, including those that may contain microbiological contaminants. For example, EC a has been correlated with concentrations of K + , Na + , Cl -, SO 4 2-, NH 4 + , and NO 3 in soils affected by animal manure wastes (Eigenberg et al, 1998;Martínez-Pagán et al 2009;Ranjan and Karthigesu, 1995;Stevens et al, 1995). By contrast, more limited research has been published on the use of geophysics for assessing contaminants resulting from wastewater treatment systems (e.g.…”
Section: Geophysical Methods Have Been Used By a Number Of Authors Fomentioning
confidence: 99%
“…Thus, changes in any of those properties can affect resistivity and thus can potentially be monitored by means of ERT. Conventional ERT surveys have been routinely used in many engineering and geological applications, such as oil prospecting (Bauman 2005;Eruteya et al 2021), geotechnical investigation (Banham and Pringle 2011;Jones et al 2012Jones et al , 2009Lopes et al 2019;Rucker et al 2009;Sentenac and Zielinski 2009), land contamination (Benson et al 1997;Deceuster et al 2013;LaBrecque et al 1996;de Lima et al 1995;Martínez-Pagán et al 2009;Ntarlagiannis et al 2016), groundwater flow (Amabile et al 2020;Jodry et al 2019;Tresoldi et al 2019), archaeological investigations (Leucci and Greco 2012;Negri et al 2008;Tonkov and Loke 2006;Ullrich et al 2007), etc. However, applications to the problem of foundation depth assessment are more limited, particularly in the case of underwater ones.…”
Section: Introductionmentioning
confidence: 99%